The impact of shocks on gender-differentiated asset dynamics in Bangladesh - Muntaha Rakib; Julia Anna Matz (University of Bonn, Center for Development Research (ZEF), 2014)
Assets are an important means of coping with adverse events in developing countries but the role of gendered ownership is not yet fully understood. This paper investigates changes in assets owned by the household head, his spouse, or jointly by both of them in response to shocks in rural agricultural households in Bangladesh with the help of detailed household survey panel data. Land is owned mostly by men, who are wealthier than their spouses with respect to almost all types of assets, but relative ownership varies by type of asset. Controlling for unobserved heterogeneity across households and looking at changes within, rather than between, households, we find that weather shocks such as cyclones adversely affect the asset holdings of household heads in general, while predicted external events lead to assets of both spouses being drawn down. The results, furthermore, suggest that jointly owned assets are not sold in response to shocks, either due to these assets being actively protected or due to the difficulty of agreeing on this coping strategy, and that womens asset holdings and associated coping strategies are shaped by their lower involvement in agriculture.
Keywords: D13; J16; O12; 330; shocks; assets; gender; ownership; coping strategies; Bangladesh